Sex differences in morphology across an expanding range edge in the flightless ground beetle, Carabus hortensis - Yarwood, Elisabeth; Drees, Claudia; Niven, Jeremy E.; Gawel, Marisa; Schuett, Wiebke (Ecology and evolution, 2021)
Species’ ranges are dynamic, changing through range shifts, contractions, and expansions. Individuals at the edge of a species’ shifting range often possess morphological traits that increase movement capacity, that are not observed in individuals farther back within the species’ range. Although morphological traits that increase in proportion toward the range edge may differ between the sexes, such sex differences are rarely studied. Here, we test the hypotheses that body size and condition increase with proximity to an expanding range edge in the flightless ground beetle, Carabus hortensis, and that these trait changes differ between the sexes. Male, but not female, body size increased with proximity to the range edge. Body size was positively correlated with male front and mid tibia length and to female hind tibia length, indicating that body size is indicative of movement capacity in both sexes. Body condition (relative to body size) decreased with increasing population density in males but not females. Population density was lowest at the range edge. Our results indicate that sex is an important factor influencing patterns in trait distribution across species’ ranges, and future studies should investigate changes in morphological traits across expanding range margins separately for males and females. We discuss the implications for sex differences in resource allocation and reproductive rates for trait differentiation across species’ shifting ranges. The distribution of morphological traits may change across species' shifting or expanding ranges. Here, we show that the differentiation of such traits is sex‐specific in the ground beetle species Carabus hortensis: Male, but not female, body size increased with proximity to the range edge.